Fragile hierarchies : the urban elites of third century Roman Egypt - Tacoma, Laurens Ernst, 1967- (Mnemosyne, Supplements, 2006)
Fragile Hierarchies deals with the world of the urban elites of third century Roman Egypt. It discusses economic, social and demographic aspects of the position of the elites of the small towns that dotted the Nile. The work combines analysis of Greek papyri with modelling techniques used in ancient history. The first part of the book analyses patterns of urbanisation, property relations and their consequences for elite formation. The second part discusses demographic aspects, patterns of inheritance and their consequences for continuity and discontinuity. The central argument of the book is that a strong social and economic hierarchy occurred side by side with a dynamic pattern of elite renewal.